A companion to Jean Renoir - Phillips, Alastair, 1963-; Vincendeau, Ginette, 1948- (Chichester, West Sussex : Wiley-Blackwell, 2013)
François Truffaut called him, simply, 'the best'. Jean Renoir is a towering figure in world cinema and fully justifies this monumental survey that includes contributions from leading international film scholars and comprehensively analyzes Renoir's life and career from numerous critical perspectives. New and original research by the world's leading English and French language Renoir scholars explores stylistic, cultural and ideological aspects of Renoir's films as well as key biographical periodsThematic structure admits a range of critical methodologies, from textual analy.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed on Apr. 30, 2013).
Keywords: Renoir, Jean, -- 1894-1979 -- Criticism and interpretation; Renoir, Jean, -- 1894-1979.; Motion picture industry -- Economic aspects; Motion pictures -- History; Renoir, Jean -- 1894-1979 -- Criticism and interpretation; ART -- Film & Video; PERFORMING ARTS -- Film & Video -- Reference; Electronic books; Criticism, interpretation, etc